2023
DOI: 10.1186/s12935-023-02951-5
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin blunted the angiogenic activity in 3D colon cancer tumoroids by the reduction of endocan

Maryam Taghavi Narmi,
Hanieh Mohajjel Shoja,
Sanya Haiaty
et al.

Abstract: Background Complexity and heterogeneity of the tumor niche are closely associated with the failure of therapeutic protocols. Unfortunately, most data have been obtained from conventional 2D culture systems which are not completely comparable to in vivo microenvironments. Reconstructed 3D cultures composed of multiple cells are valid cell-based tumor models to recapitulate in vivo-like interaction between the cancer cells and stromal cells and the oncostatic properties of therapeutics. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The current trend in new drug design involves the utilization of 3D organoids for discovering the effects of the drugs. Previous studies have demonstrated that the application of melatonin in 3D cultures presents considerable potential therapeutic efficacy for comprehending the antitumor effects aimed at blunting angiogenic activity 46 . Our data indicated that melatonin has the potential to restore endothelial function not only in in vitro experiments but also in EndMT‐induced VOs.…”
Section: Discussionmentioning
confidence: 55%
“…The current trend in new drug design involves the utilization of 3D organoids for discovering the effects of the drugs. Previous studies have demonstrated that the application of melatonin in 3D cultures presents considerable potential therapeutic efficacy for comprehending the antitumor effects aimed at blunting angiogenic activity 46 . Our data indicated that melatonin has the potential to restore endothelial function not only in in vitro experiments but also in EndMT‐induced VOs.…”
Section: Discussionmentioning
confidence: 55%
“…The promise that exists now is that cells cultivated in three-dimensional aggregates have the capacity to increase resistance to different cancer treatments. Recent research by Narmi et al in 2023, which discovered that using 3D culture is an efficient way to evaluate anticancer drugs, has supported this work [ 16 ]. Various priming techniques have been developed that aim to sensitize cells and get them ready for therapeutic treatment.…”
Section: Introductionmentioning
confidence: 81%
“…This provides a more representative platform for researching these methods [ 11 , 17 ]. In 2023 Narmi and colleagues discovered that the use of melatonin in three-dimensional culture has significant promise for comprehending the anti-tumour activity exhibited by melatonin in reaction to certain angiogenesis elements [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was stated that the 3D tumoroid system is a promising approach for the assessment of anti-cancer compounds as compared to the conventional 2D culture system and melatonin was able to significantly decrease the cohesion of tumor mass through the arrest of some angiogenesis agents such as endocan with simultaneous induction of necrotic variations. 45 …”
Section: Cell Culture Methods In Vitromentioning
confidence: 99%